Planoscalpellum planum - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
Planoscalpellum planum (Hoek, 1883) Fig. 23 Scalpellum planum Hoek, 1883: 116, pl. IV, figs 12–13; Murray, 1896: 362; Weltner, 1897: 249; 1900: 307; Gruvel, 1902b: 248; 1905: 87, fig. 97; Schmalz, 1906: 69; Nilsson-Cantell, 1955: 218. Planoscalpellum planum : Zevina, 1978b: 1347; 1981a: 185–186; 1981b: 89; Jones et al. , 1990: 4; Jones, 1991: 153; 2012: 371, 376; Young, 2007: 39–41, figs 47–49, table 10. Material examined. Holotype (dry) NHM UK 2013.1112, Stn 160: Indian Ocean, Eastern; 4758 m. Supplementary description. Young (2007). Distribution. Indian Ocean, Eastern; Pacific, Eastern Central: off Costa Rica, Gulf of Panama. Known depth range 421 to 4758 m. Remarks. The holotype is dry and in poor condition. Designating a neotype is probably advisable in order to stabilise its nomenclature. Genus Teloscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part); Pilsbry, 1907a: 47; Newman & Ross, 1971: 42 (part). Teloscalpellum Zevina, 1978b: 1350. Diagnosis. Capitulum with 13 or 14 plates; inframedian latus triangular or rod-shaped, umbo apical or sub-apical; carinal latus umbo at basi-carinal angle, not or only slightly extending beyond carinal margin caudal appendage typically multi-segmented (up to nine segments), sometimes one segment or none. Type species. Scalpellum spicatum Zevina, 1975. Composition. 18 species. Distribution. Worldwide, except Arctic; known depth range 90 to 4758 m. Remarks. Zevina (1978b) pointed out that only the basicarinal umbo of the carinal latus distinguishes this genus from Arcoscalpellum , Trianguloscalpellum Zevina, 1978, Anguloscalpellum and Diceroscalpellum Zevina, 1978. Young (1999a) overlooked this genus in his preliminary re-assessment of the Scalpellidae, but did include it in his later assessment (Young, 2007). At present, the phylogenetic position of Teloscalpellum among other genera of the subfamily Arcoscalpellinae has yet to be established. Genus Teloscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part); Pilsbry, 1907a: 47; Newman & Ross, 1971: 42 (part). Teloscalpellum Zevina, 1978b: 1350. Diagnosis. Capitulum with 13 or 14 plates; inframedian latus triangular or rod-shaped, umbo apical or sub-apical; carinal latus umbo at basi-carinal angle, not or only slightly extending beyond carinal margin caudal appendage typically multi-segmented (up to nine segments), sometimes one segment or none. Type species. Scalpellum spicatum Zevina, 1975. Composition. 18 species. Distribution. Worldwide, except Arctic; known depth range 90 to 4758 m. Remarks. Zevina (1978b) pointed out that only the basicarinal umbo of the carinal latus distinguishes this genus from Arcoscalpellum , Trianguloscalpellum Zevina, 1978, Anguloscalpellum and Diceroscalpellum Zevina, 1978. Young (1999a) overlooked this genus in his preliminary re-assessment of the Scalpellidae, but did include it in his later assessment (Young, 2007). At present, the phylogenetic position of Teloscalpellum among other genera of the subfamily Arcoscalpellinae has yet to be established. : Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS " Challenger " expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on pages 36-37, DOI: 10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932 : {"references": ["Hoek, P. P. C. (1883) Report on the Cirripedia collected by H. M. S. \" Challenger \" during the years 1873 - 1876. Systematic part. Report on the Scientific Results of the Voyage H. M. S. \" Challenger \", during the years 1873 - 7, Zoology, part 25 (8), 1 - 169.", "Murray, J. (1896) On the deep and shallow-water marine fauna of the Kerguelen region of the great Southern Ocean. Transactions of the Royal Society of Edinburgh, 38 (2), 343 - 500.", "Weltner, W. (1897) Verzeichnis der bisher beschriebenen recenten Cirripedienarten. Mit Angabe der im berliner Museum vorhandenen Species und ihrer Fundorte. Archiv fur Naturgeschichte, 63 (1), 227 - 280.", "Weltner, W. (1900) Die Cirripedien der Arktis. Fauna Arctica, 1, 287 - 312.", "Gruvel, A. (1902 b) Revision des Cirrhipedes appartenant a la collection du Museum d'Histoire naturelle. Pedoncules. I. Partie systematique. Nouvelles Archives du Museum d'Histoire naturelle, Paris, Series 4, 4, 215 - 312.", "Gruvel, A. (1905) Monographie des Cirrhipedes ou Thecostraces. Masson et Cie (editeurs), Libraire de l'Academie de Medicine, Paris, 472 pp.", "Schmalz, C. (1906) Die Ordnung der Cirripedien. Bauer & Raspe, Nurnberg, 82 pp.", "Nilsson-Cantell, C. A. (1955) Cirripedia. Reports of the Swedish Deep Sea Expedition 2. Zoology, 17, 215 - 220.", "Zevina, G. B. (1978 b) A new classification of the Scalpellidae (Cirripedia, Thoracica). Part 2 Subfamilies Arcoscalpellinae and Meroscalpellinae. Zoologicheskii Zhurnal, 57 (9), 1343 - 1352. [in Russian]", "Zevina, G. B. (1981 a) Cirriped crustaceans of the suborder Lepadomorpha (Cirripedia, Thoracica) of the World Ocean. Part 1. Family Scalpellidae. Opredeliteli po Faune SSSR, Leningrad, 398 pp. [in Russian]", "Zevina, G. B. (1981 b) [Deep-sea Cirripedia of the Australian and New Zealand waters.] Trudy Instituta Okeanologii, 115, 76 - 93. [in Russian]", "Jones, D. S., Anderson J. T. & Anderson, D. T. (1990) A checklist of the Australian Cirripedia (Thoracica, Acrothoracica). Technical Reports of the Australian Museum, 3, 1 - 38.", "Jones, D. S. (1991) A history of the discovery and description of Australian barnacles (Cirripedia: Thoracica), including a bibliography of reference works. Archives of Natural History, 18 (2), 149 - 178. http: // dx. doi. org / 10.3366 / anh. 1991.18.2.149", "Jones, D. S. (2012) Australian barnacles (Cirripedia: Thoracica), distributions and biogeographical affinities. Integrative and Comparative Biology, 52 (3), 366 - 387. http: // dx. doi. org / 10.1093 / icb / ics 100", "Young, P. S. (2007) The Scalpellomorpha (Crustacea, Cirripedia), with a list of extant species (except the Calanticidae). Galathea Report, 21, 7 - 73.", "Hoek, P. P. C. (1907) The Cirripedia of the Siboga expedition A. Cirripedia Pedunculata. Siboga Expeditie Monographe, 31 (a), 1 - 127.", "Pilsbry, H. A. (1907 a) The Barnacles (Cirripedia) contained in the collections of the U. S. National Museum. Bulletin of the United States National Museum, 60, 1 - 122. http: // dx. doi. org / 10.5479 / si. 03629236.60.1", "Newman, W. A. & Ross A. (1971) Antarctic Cirripedia. Antarctic Research Series, 14. American Geophysical Union, Washington, 257 pp.", "Zevina, G. B. (1975) Cirripedia Thoracica of the American north west Atlantic.] Trudy Instituta Oceanologii Akademii Nauk SSSR, 100, 233 - 258. [in Russian]", "Young, P. S. (1999 a) A preliminary assessment of the characters used in the definitions of the subfamilies at present included in the Scalpellidae Pilsbry, 1907 sensu Newman, 1996 (Cirripedia, Thoracica). In: Schram, F. R. & von Vaupel, J. C. (Eds.), Crustaceans and the biodiversity crisis. Vol. 1. Proceedings of the Fourth International Crustacean Congress, Amsterdam, The Netherlands, 20 - 24 July 1998. Brill, Leiden, pp. 173 - 193."]}